The effect of steering axis inclination on the dynamic stability of vehicles with an articulated steering - Aleksander Skurjat (Scientific Reports)
Abstract The phenomenon of snaking of vehicles can be caused by many factors. It results from the loss of the vehicle’s straight-line direction of motion, which is intended by the driver. In this situation, for single-mass vehicles (like automobiles), special systems (braking) are activated, aiming to return the vehicle to the direction intended by the driver. Additionally, in automobiles wheel caster angle is applied to facilitate maintaining the straight-line direction. However, for articulated vehicles where two masses are connected by articulated joint, such solutions cannot be applied directly because they are complicated. The paper undertakes an analysis of whether an inclined steering axis in vehicles with articulated steering systems will allow to obtain the additional torque to automatically return to rectilinear motion.For this purpose, a mathematical model was developed, and the influence of: the tilt of the articulation joint axis, changes in the position of the centre of gravity of the front and rear frames, tyre stiffness and damping, and steering system stiffness and damping in the vehicle’s trajectory were analysed. The mathematical model consists of six submodels: kinematic model, dynamic model, tyre model, steering system model, front rear yaw angle division model, and solution evaluation method. The research showed that applying a tilt of the articulation joint axis can either positively or negatively affect the resulting direction of motion, and it depends on the adopted vehicle parameters.